A new species of Golinca Thomson (Coleoptera: Scarabaeidae: Cetoniinae): first record of the genus for Brazil - Valois, M.; Silva, F. (Zootaxa, 2015)
Golinca trevisani Valois & Silva, new species (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini: Incina) from Ouro Preto do Oeste, Rondônia, and Amazonas, Brazil is described, representing the first record of the genus Golinca for Brazil. Diagnosis, illustrations of key morphological characters, the first male genitalia description in the genus, and a key for identification of four species of Golinca are provided.